Retirement reforms laws : a comparative study between South Africa and Chile - Mamabolo, Michael Makebe (My University, 2015)
This mini-dissertation discusses the retirement reforms laws. It analysis the comparative study between South Africa and Chile. South Africa had undergone the retirement reforms processes since 1992 when Mouton Commission of Inquiry was established and in 2002. Since then lot of discussion papers were finalised which mooted retirement reforms ranging from retirement reforms and social security, a safer financial sector to serve South Africa better, strengthening retirement savings, costs of retirement benefits. Chile is a country which is already ahead in their retirement reforms processes. This study seeks to evaluate the lessons which South Africa can learn from Chile so that they can fast-track their retirement reforms and re-write the new Pension Funds Act which incorporate both public and private sectors.
Thesis (LLM.) -- University of Limpopo, 2015
Keywords: Retirement reforms laws; Postemployment benefits; Pensions; Retirement -- South Africa; Retirement -- Chile